2018
DOI: 10.1177/0031512518809203
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance and Fall Risk in Persons With Traumatic Brain Injury

Abstract: Injuries sustained from traumatic brain injury (TBI) culminate in both cognitive and neuromuscular deficits. Patients often progress to higher functioning on the Rancho continuum even while mobility deficits persist. Although prior studies have examined physical performance among persons with chronic symptoms of TBI, less is known about the relatively acute phase of TBI as patients prepare for rehabilitation discharge. The aims of this cross-sectional study were to (a) compare balance and gait performance in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…One reason for a relative lack of understanding of imbalance in TBI is that there are no acute prospective studies (mechanistic or otherwise) assessing vestibular dysfunction in acute TBI. There has been one cross-sectional study assessing instrumented measures of balance, in the subacute stage ( Klima et al , 2019 ) confirming manifest imbalance in subacute TBI. We also recently reported two separate cross-sectional clinical studies in ambulant acute TBI patients; one showing that 62% were unbalanced ( Marcus et al , 2019 ) of whom half did not report feeling unbalanced, and the other ( Sargeant et al , 2018 ), confirming the lack of correlation between objective signs of imbalance and vestibular symptom scores.…”
Section: Introductionmentioning
confidence: 97%
“…One reason for a relative lack of understanding of imbalance in TBI is that there are no acute prospective studies (mechanistic or otherwise) assessing vestibular dysfunction in acute TBI. There has been one cross-sectional study assessing instrumented measures of balance, in the subacute stage ( Klima et al , 2019 ) confirming manifest imbalance in subacute TBI. We also recently reported two separate cross-sectional clinical studies in ambulant acute TBI patients; one showing that 62% were unbalanced ( Marcus et al , 2019 ) of whom half did not report feeling unbalanced, and the other ( Sargeant et al , 2018 ), confirming the lack of correlation between objective signs of imbalance and vestibular symptom scores.…”
Section: Introductionmentioning
confidence: 97%
“…Both etiologies lead to dynamic balance impairments (McCulloch et al, 2010; Lord et al, 2004). Dynamic balance impairment is a risk factor for falls post-ABI, and has a significant impact on physical function, activity, community participation and quality of life years after the injury (McCulloch et al, 2010; Lord et al, 2004; Peterson et al, 2015; Klima et al, 2019; Medley et al, 2006). About 30% to 65% of TBI survivors and 73% of community-dwelling stroke survivors, report continual problems in dynamic balance control and gait (Klima et al, 2019, Forster et al, 1999) and a fall within 6 months post-stroke (Yates et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic balance impairment is a risk factor for falls post-ABI, and has a significant impact on physical function, activity, community participation and quality of life years after the injury (McCulloch et al, 2010; Lord et al, 2004; Peterson et al, 2015; Klima et al, 2019; Medley et al, 2006). About 30% to 65% of TBI survivors and 73% of community-dwelling stroke survivors, report continual problems in dynamic balance control and gait (Klima et al, 2019, Forster et al, 1999) and a fall within 6 months post-stroke (Yates et al, 2002). ABI survivors demonstrate also reduced gait stability and adjustments of gait patterns when faced with environmental challenges, such as avoiding obstacles (Hyndman et al, 2006; Van Swigchem et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies indicated an association between brain atrophy post-stroke and gait control decline [7,8] and increased risk of motor-related neurodegenerative disorders such as Parkinson disease post-TBI [9] . Subjects post-ABI at the chronic phase frequently suffer from a dynamic balance control impairment which restricts their mobility, limits their community integration and their locomotor abilities [10][11][12] . Dynamic balance control is a complex function that is achieved by both feedback and feedforward control mechanisms and mediated by both central pattern generation at the spinal level and subcortical and cortical brain areas [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%